Advances in the pathophysiology of adult-onset focal dystonias: recent neurophysiological and neuroimaging evidence - Conte, Antonella (F1000Res, 2020)
Focal dystonia is a movement disorder characterized by involuntary muscle contractions that determine abnormal postures. The traditional hypothesis that the pathophysiology of focal dystonia entails a single structural dysfunction (i.e. basal ganglia) has recently come under scrutiny. The proposed network disorder model implies that focal dystonias arise from aberrant communication between various brain areas. Based on findings from animal studies, the role of the cerebellum has attracted increased interest in the last few years. Moreover, it has been increasingly reported that focal dystonias also include nonmotor disturbances, including sensory processing abnormalities, which have begun to attract attention. Current evidence from neurophysiological and neuroimaging investigations suggests that cerebellar involvement in the network and mechanisms underlying sensory abnormalities may have a role in determining the clinical heterogeneity of focal dystonias.